Small noncoding RNA modulates japanese encephalitis virus replication and translation in trans - Fan, Yi-Hsin; Nadar, Muthukumar; Chen, Chiu-Chin; Weng, Chia-Chen; Lin, Yun-Tong; Chang, Ruey-Yi (Virology journal, 2011)
Sequence and structural elements in the 3'-untranslated region (UTR) of Japanese encephalitis virus (JEV) are known to regulate translation and replication. We previously reported an abundant accumulation of small subgenomic flaviviral RNA (sfRNA) which is collinear with the highly conserved regions of the 3'-UTR in JEV-infected cells. However, function of the sfRNA in JEV life cycle remains unknown. Northern blot and real-time RT-PCR analyses indicated that the sfRNA becomes apparent at the time point at which minus-strand RNA (antigenome) reaches a plateau suggesting a role for sfRNA in the regulation of antigenome synthesis. Transfection of minus-sense sfRNA into JEV-infected cells, in order to counter the effects of plus-sense sfRNA, resulted in higher levels of antigenome suggesting that the presence of the sfRNA inhibits antigenome synthesis. Trans-acting effect of sfRNA on JEV translation was studied using a reporter mRNA containing the luciferase gene fused to partial coding regions of JEV and flanked by the respective JEV UTRs. In vivo and in vitro translation revealed that sfRNA inhibited JEV translation. Our results indicate that sfRNA modulates viral translation and replication in trans.